ΟΙ ΠΡΟΤΕΣΤΑΝΤΙΚΕΣ ΙΔΕΕΣ, Ο MARK TWAIN ΚΑΙ ΤΟ ΠΡΟΤΥΠΟ TOΥ ΠΑΙΔΙΚΟΥ ΧΑΡΑΚΤΗΡΑ ΣΤΟ ΜΙΣΣΙΟΝΑΡΙΚΟ ΒΙΒΛΙΟ ΣΤΗΝ ΕΛΛΑΔΑ (19ΟΣ ΑΙ.) - ΘΑΝΑΗΛΑΚΗ, ΠΟΛΛΗ (Μνήμων, 2005)
Polly Thanailaki, The protestant ideas, Mark Twain and the model of the child's character in the missionary books in Greece in the 19th century This essay explores the historical evolution which was observed in the shaping of the child's model of character in the American literature books of the 19th century within the frame of the protestant ideas and values. It also studies the impact of this development in the missionary books for children in Greece in the same century. We particularly focus on Mark Twain's revolutionary presence in the American children's literature by, firstly, placing emphasis on the change that the great American author made to the strict puritan model with the shaping of a more liberal and «innocent» children's character and, secondly, by analyzing the response which Twain's books met from the Greek 19th century readers. In this paper we argue that Twain's writing, known for realism, biting social satire and memorable children's characters, influenced the Greek children's literature in the end of the 19th century. The translations of his works started taking the lead in the end of this century in Greece. Moreover, this essay studies the re-shaping of the child's character in the missionary books published in Greece in the mid 19th century. The missionaries also followed the new trend for the children's character. The missionary stories appeared less didactic and strict.